THU0153 The effect of 5-years b-dmards treatment on different 10-years cardiovascular risk scores applied in rheumatoid arthritispatients. (12th June 2018) - Cacciapaglia, F.; Fornaro, M.; Renna, D.; Cafarelli, F.; Lopalco, G.; Anelli, M.G.; Scioscia, C.; Lapadula, G.; Iannone, F.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an excess risk of cardiovascular (CV) disease. Objectives: We aimed to assess whether 5 years treatment with biologic DMARDs can impact on the 10 year CV risk assessed with different scores. Methods: In this monocentric study we retrospectively evaluated data available at 2012 and 2017 to calculate the CV scores according to the Italian CV risk score Cuore project, 1 QRISK2–2017 score 2 and the score proposed by Solomon DH et al.. 3 Moreover, RA characteristics were registered and correlated to the risk scores at baseline and after 60 months of treatment with RA approved biologic agents. Any CV event was registered. Results: 110 patients with RA treated for the first time with a bDMARDs, and no prior CV events were included (mean age 52±11.3 years; 80% women; median disease duration 36 months). During the evaluated period 47 (42%) patients switched to a different bDMARD, 10 (9%) patients stopped the treatment for side effects and 3 (2.7%) patients with high CV risk scores at baseline presented a CV event within 4 years (2 myocardial infarction and 1 stroke). At baseline we observed a mean CV risk of 3.69 (95% confidence interval [CI], 2.70–4.68) assessed as moderate by the Cuore project, 10.64 (95%CI 8.48–12.8) and 10.43 (95%CI 8.61–12.24) considered as high risk according to the QRISK2–2017 and Solomon's scores, respectively. After 5 years we recorded a significant increase in CV risk assessed by the Cuore project and the QRISK2–2017 score [4.20 (95%CI 3.23–5.18) and 13.12 (95%CI 10, 72–15, 53), respectively; p<0.001 vs baseline]. In comparison with baseline the change in the Solomon's score did not reach the statistical significance [10.68 (95%CI 8.78–12.58); p=0.66]. In 38 (39.2%) patients that achieved persistent CDAI remission/low disease activity during the entire 5 years follow-up we observed a statistically significant reduction in the Cuore project score [4.1 (95%CI 2.1–6) vs 3.8 (95%CI 2.3–5.3); p=0.02) and in the Solomon's score [9.3 (95%CI 5.6–13) vs 7.8 (95%CI 5.2–10.5); p=0.04). No statistical significance was found in CV risk scores stratifying patients for disease duration, RA specific disease characteristics, and mechanism of action and/or number of switch in bDMARD treatment. Conclusions: RA patients are at moderate/high CV risk as assess by the different CV risk scores used, more consistent if inflammatory or disease specific items are considered in the score. Sustained CDAI remission obtained with bDMARDs can invert CV risk progression for 5 years estimated by Cuore project and Solomon's score, despite ageing. References: [1] Palmieri L, et al. CUORE project: implementation of the 10-year risk score. Eur J Cardiovasc Prev Rehabil2011;18:642–9. [2] Hippisley-Cox J, et al. Predicting cardiovascular risk in England and Wales: prospective derivation and validation of QRISK2. BMJ2008;336:a332. [3] Solomon DH, et al. Derivation and internal validation of an expanded cardiovascular risk prediction score for rheumatoid arthritis: a Consortium of Rheumatology Researchers of North America Registry Study. Arthritis Rheumatol2015;67:1995–2003. Disclosure of Interest: None declared